Patterns of in vitro activity of itraconazole and imidazole antifungal agents against Candida albicans with decreased susceptibility to fluconazole from Spain. - Martinez-Suarez, J V (1995)
Two groups of recent clinical isolates of Candida albicans consisting of 101 isolates for which fluconazole MICs were < or = 0.5 microgram/ml (n = 50) and > or = 4.0 micrograms/ml (n = 51), respectively, were compared for their susceptibilities to fluconazole, clotrimazole, miconazole, ketoconazole, and itraconazole. Susceptibility tests were performed by a photometer-read broth microdilution method with an improved RPMI 1640 medium supplemented with 18 g of glucose per liter (RPMI-2% glucose; J. L. Rodríguez-Tudela and J. V. Martínez-Suárez, Antimicrob. Agents Chemother. 38:45-48, 1994). Preparation of drugs, basal medium, and inocula was done by the recommendations of the National Committee for Clinical Laboratory Standards. The MIC endpoint was calculated objectively from the turbidimetric data read at 24 h as the lowest drug concentration at which growth was just equal to or less than 20% of that in the positive control well (MIC 80%). In vitro susceptibility testing separated azole-susceptible strains from the strains with decreased susceptibilities to azoles if wide ranges of concentrations (20 doubling dilutions) were used for ketoconazole, miconazole, and clotrimazole. By comparison with isolates for which fluconazole MICs were < or = 0.5 microgram/ml, those isolates for which fluconazole MICs were > or = 4.0 micrograms/ml were in general less susceptible to other azole drugs, but different patterns of decreased susceptibility were found, including uniform increases in the MICs of all azole derivatives, higher MICs of several azoles but not others, and elevated MICs of fluconazole only. On the other hand, decreased susceptibility to any other azole drug was never found among strains for which MICs of fluconazole were lower.